2016
DOI: 10.1016/j.algal.2016.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive metabolic reprograming in freshwater Nitzschia palea strains undergoing nitrogen starvation is likely associated with its ecological origin

Abstract: Nitrogen deficiency can increase the lipid content in certain microalgae species, including diatoms. However, the molecular and metabolic basis of such changes remains rather unclear. We analyzed strains of freshwater Nitzschia palea collected from a eutrophic pond and from an artificial rock. The habitats, differing in light and nutrient availability, lead to two metabolically distinct strains, BR006 and BR022. Differential accumulation of primary compounds, membrane lipid composition and fatty acid saturatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 74 publications
0
9
0
Order By: Relevance
“…Spectra obtained from 1/4X NO 3 cultures were not as sharp as spectra obtained from other treatment cultures. Broad spectra are indicative of heavy molecular weight components inside the extract sample 15 , 33 , 34 . A possible higher relative concentration of sugar or starch granules (in comparison to other metabolites) may have accumulated within the microalgae cell as microalgae cells have been acknowledged to synthesis starch under nitrate starved conditions 8 , 35 , 36 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Spectra obtained from 1/4X NO 3 cultures were not as sharp as spectra obtained from other treatment cultures. Broad spectra are indicative of heavy molecular weight components inside the extract sample 15 , 33 , 34 . A possible higher relative concentration of sugar or starch granules (in comparison to other metabolites) may have accumulated within the microalgae cell as microalgae cells have been acknowledged to synthesis starch under nitrate starved conditions 8 , 35 , 36 .…”
Section: Resultsmentioning
confidence: 99%
“…Scenedesmus regularis (KS-MC1) was obtained from Institute of Marine Biotechnology (IMB) of Universiti Malaysia Terengganu. The culture and maintenance of Scenedesmus regularis was adopted from 34 . In nitrate treatment, the concentration for NaNO 3 was altered while the other components remained the same as in Guillard’s F2 media.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cladophora influences the process of P exchange in sediments in Rongcheng Swan Lake, and this can significantly promote the release of P from the sediment (Gao et al, ). Prior studies have also shown that microalgae can effectively utilise nutrients in the water, including N and P, aiding in their growth and reproduction (Machado et al, ). As such, it can be surmised that Nitzschia sp .…”
Section: Introductionmentioning
confidence: 99%